(untitled) (Studia Prawnicze / The Legal Studies, 1985)
In the modern theory of law Jerzy Wróblewski suggested to introduce a category of relative facts into the theory of legal facts. The article contributes to those problems and tries to find out to what degree they are in line with Leibniz’s views. This is also connected with the question considered by Leibniz whether “moral beings” are relations and whether relations are real or relational beings. The result is Leibniz’s thesis: omnis lex preasumptionem habet. The thesis led Leibniz to the theory of relative facts: “ex iure oritur factum”.